Phytotoxic Effects of Fluoride on Crop Plants: A Review - Chakrabarti, Sakuntala; Patra, Pulak Kumar; Mandal, Bhabatosh (Asian Journal of Biological and Life Sciences, 2017)
Fluoride is a common element on the earth's crust and exists naturally in soil, water and air. The elevated concentrations of fluoride in environment have been found to affect adversely the health of humans, animals and plants in many parts of the world. Fluoride is not an essential element for plants. However, plants can uptake fluoride from the fluoride contaminated environment, either through the roots from the soil zone or by the stomata from the atmospheric deposits on leaves. The use of fluoride-contaminated groundwater for irrigation is a major concern in many fluoride endemic areas. It results fluoride accumulation in the plant parts which ultimately enter the food chain and increases the risk of fluorosis in the area which is already affected by F- rich drinking water. Besides F-uptake, plants also undergo major physiological, metabolically and biochemical alterations by prolonged exposure to fluoride. The present review compiles the available information of the effect of fluoro-toxicity on seed germination, growth and productivity, pigments, metabolites and biomolecules in crop plants. The paper highlights the adaptive response of different crop plants to F- stress, the knowledge of which will be useful for future research in developing F-resistant crop varieties or mitigating the F-stress in crop plants.
Keywords: Antioxidants; Fluoride toxicity; Fluoride uptake; Growth responses; Oxidative stress